Diffuse Astrocytoma, IDH-Wildtype: A Dissolving Diagnosis. Issue 6 (9th February 2018) - Hasselblatt, Martin; Jaber, Mohammed; Reuss, David; Grauer, Oliver; Bibo, Annkatrin; Terwey, Stephanie; Schick, Uta; Ebel, Heinrich; Niederstadt, Thomas; Stummer, Walter; von Deimling, Andreas; Paulus, Werner
Abstract: The histological and molecular features and even the mere existence of diffuse astrocytoma, IDH-wildtype, remain unclear. We therefore examined 212 diffuse astrocytomas (grade II WHO) in adults using IDH1(R132H) immunohistochemistry followed by IDH1/IDH2 sequencing and neuroimaging review. DNA methylation status and copy number profiles were assessed by Infinium HumanMethylation450k BeadChip. Only 25/212 patients harbored tumors without IDH1/IDH2 hotspot mutations and without contrast enhancement. By DNA methylation profiling, 10/25 tumors were classified as glioblastoma, IDH-wildtype, and an additional 7 cases could not be classified using methylome analysis, but showed genetic characteristics of glioblastoma. Histologically, all of these 17 tumors were low-grade diffuse astrocytomas. Nevertheless, 10/17 patients experienced early malignant progression. Other methylation classes included diffuse midline glioma, H3 K27M-mutant, diffuse astrocytoma, IDH-mutant, pilocytic astrocytoma, and normal or reactive brain tissue (total n = 8). In conclusion, no convincing diffuse astrocytoma, IDH-wildtype, was identified. Most IDH-wildtype tumors showing histopathological and radiological features of low-grade diffuse astrocytoma exhibit molecular and clinical features of high-grade glioma and may represent an early stage of primary glioblastoma. Our findings have implications for the biology, classification and neuropathological diagnosis of diffuse astrocytoma, IDH-wildtype in adults.